Efektivitas Penggunaan Twitter Sebagai Sarana Peningkatan Berpikir Kritis Mahasiswa Ilmu Komunikasi - Rahmania Mustaqlillah; Okky Widyaningtyas; Tri Wantoro (MUKASI: Jurnal Ilmu Komunikasi, 2023)
Twitter is a social media that is widely used by teenagers and parents, especially students. Twitter is a well-known social media where users are free to express their opinions, interactions between individuals are often built between users. The Tweet and Retweet features are a factor in building interaction and broad reach. All social phenomena that occur in the social environment are easily known if social media users skate with Twitter. This study aims to find out whether the use of social media Twitter can be used as a means to improve students' critical thinking in communication science students at No University. The research was conducted using a quantitative descriptive approach. The research data is primary data, namely a questionnaire with a purposive sampling technique and a sample of 100 respondents. Data is processed using SPSS, by performing simple linear regression analysis, data quality test, normality test, regression test and t test. The results showed that the effectiveness of using Twitter had a positive and significant influence on improving the critical thinking of communication science students at Tidar University.